Permeability and selectivity of hybrid membrane (PES/PSU) for gas separation - Mohd Izwan, Mohd (2009)
A hybrid membrane (PES/PSU) was prepared through a simple dry/wet phase inversion process. The casting solution developed in this research consists of PES, PSU, 1-methyl-2-pyrolidone (NMP) and methanol. Hybrid membrane (PES/PSU) is divided into three categories; uncoated, coated with polydimethylsiloxane (PDMS) and coated with bromine solution. Permeation test was carried out by testing CO2, CH4, N2 and O2 onto the hybrid membrane to see the permeability and selectivity of the respective gas to CH4. Different coating agent gives different rate of permeate to the hybrid membrane. The hybrid membrane (PES/PSU) that coated with PDMS shows higher selectivity compared to conventional hybrid membrane and hybrid membrane that coated with bromine solution. The selectivity of CO2/CH4 is approximately 0.563, it is believed that different coating agent strongly affects the hybrid membrane performance.-Author-